Expanding heme-protein folding space using designed multi-heme β-sheet mini-proteins - D’Souza, Areetha (2019)
Nature has primarily exploited helical proteins, over β-sheets, for heme/multi-heme coordination. Understating of heme–protein structures has motivated the design of heme proteins utilizing coiled-coil helical structure. By contrast, de novo designed β-sheet proteins are less successful. However, designing proteins with discretely folded β-sheet structures encoding specific functions would have great potential for the development of new synthetic molecules e.g. enzymes, inhibitors. Here we report the design and characterization of multi-heme binding four-, six-, eight-, and twelve-stranded β-sheet mini-proteins (<40 amino acids) and proteins. Atomic-resolution structures demonstrate an expected β-sheet structural topology. The designed β-sheet mini-proteins pack or latch multiple hemes with high affnity in versatile orientations either by stacking or sideways, mimicking naturally occuring multi-heme protein conduits. The designed multi-stranded β-sheet heme proteins could serve as a platform for the generation of novel synthetic β-sheet protein mimics.